轉上市能增加媒體能見度嗎？ - 洪榮耀; 馬黛; Jung-Yao Hung; Tai Ma (My University, 2006)
本文是國內首篇研究自中華民國櫃檯買賣中心移轉至台灣證券交易所之公司其媒體能見度變化，並以此變化來瞭解轉上市是否能增加公司能見度。我們針對1999，2000，2001及2003年台灣證券市場轉上市公司，以公司名稱被刊於平面媒體之次數做為公司媒體能見度指標，進行公司媒體能見度提升之相關分析。實證結果有三個主要發現，(1)公司藉由轉上市可提升其媒體能見度。(2)上櫃時間長短及資本額大小與能見度效果互為反向。(3)台灣證券市場轉上市公司之媒體能見度提升是與轉上市有關，而非來自盈餘成長或市值成長。本文結果可與Baker and Pettit (1982), Baker and Johnson (1990)提出之管理者以能見度作為上市動機相互對應，並確認了Arbel and Strebel (1982，1983)，Carvel and Strebel (1987), Christie and Huang (1994)及Baker et al. (1999b)之較受忽略之公司轉上市效益較大之主張，但與Dharan and Ikenberry (1995)，Baker et al (1998)及Baker et al. (1999a)指稱之盈餘成長或市值成長能增加公司能見度並不相同。

This study is the first domestic paper to investigate the effect of media visibility on the firms switching location from the GreTai Securities Market (OTC) to the Taiwan Stock Exchange Corporation (TSEC). This paper analyzes the visibility improvement of the firms conducting exchange listing from 1999 to 2003, using media exposure as the indicator of a firm's visibility. The empirical study has three math findings: (1) Exchange listing ca improve media visibility. (2) The trading age iii the OTC market mid the capital scale have inverse influences on visibility effect. (3) The visibility effect of Taiwan's exchange listed firms should be related to exchange listing, lot growth of earnings or growth of market capitalization The results of this paper correspond to the conclusion of Baker and Pettit (1982) mid Baker and Johnson (1990) that management's intention of exchange listing is visibility, and also confirm the finding of Arbel and Strebel (1982, 1983), Carvel and Strebel (1987), Christie and Huang (1994), and Baker et al. (1999b) that the exchange listing effect is higher on those relatively ignored firms. Nevertheless, our results differ from the finding of Dharan and Ikenberry (1995), Baker et al (1998), and Baker et al. (1999a) that earnings or market capitalization growth can increase a firm's visibility.
Can Exchange Listing Improve Media Visibility?
Keywords: 上櫃轉上市; 能見度; 資本成長; 盈餘成長; exchange listing; visibility; growth of market capitalization; growth of earnings